Morphology, Characterization and Distribution of Retinal Photoreceptors in the South American (Lepidosiren paradoxa) and Spotted African (Protopterus dolloi) Lungfishes - Appudurai, Audrey M.; Hart, Nathan S.; Zurr, Ionat; Collin, Shaun P. (Frontiers in Ecology and Evolution, 2016)
Lungfishes are the closest living relatives of the ancestors to all terrestrial vertebrates and have remained relatively unchanged since the early Lochkovin period (410 mya). Lungfishes, therefore, represent a critical stage in vertebrate evolution and their sensory neurobiology is of considerable interest. This study examines the ultrastructure of the retina of two species of lungfishes: the South American lungfish, Lepidosiren paradoxa and the spotted African lungfish, Protopterus dolloi in an attempt to assess variations in photoreception in these two ancient groups of sarcopterygian (lobe-finned) fishes. In juvenile P. dolloi, the retina contains one rod and two cone photoreceptor types (one containing a red oil droplet), while only one rod and one cone photoreceptor type is present in adult L. paradoxa. Both species lack double cones. The large size and inclusion of oil droplets in both species apart from one of the cone photoreceptor types in P. dolloi suggests that L. paradoxa and P. dolloi are adapted for increasing sensitivity. However, the complement of photoreceptor types suggests that there may be a major difference in the capacity to discriminate colour (dichromatic and monochromatic photoreception in P. dolloi and L. paradoxa, respectively). This study suggests that the visual needs of these two species may differ.